2003
DOI: 10.1148/radiol.2283020872
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neck and Body Metastases to Nodes with Ferumoxtran 10–enhanced MR Imaging: Phase III Safety and Efficacy Study

Abstract: Ferumoxtran 10-enhanced MR imaging was safe and effective and facilitated improved diagnostic performance. Use of iron oxide-enhanced MR imaging increased the positive predictive value by 20% and the accuracy by 14% compared with reader assessment. Differentiating patients with no nodal metastatic involvement was more reliable with ferumoxtran 10-enhanced MR imaging than with precontrast MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
173
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(177 citation statements)
references
References 29 publications
3
173
1
Order By: Relevance
“…The absence of SPIO in lymph nodes as determined by MR imaging has been shown to correlate with disturbances in lymph node flow or architecture due to the presence of metastases. The T2 shortening due to SPIO accumulation was pronounced in normal nodes, allowing for significant increases in positive predictive values and accuracy of diagnosis of node metastases 3 (Fig. 2).…”
Section: Lymph Node Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of SPIO in lymph nodes as determined by MR imaging has been shown to correlate with disturbances in lymph node flow or architecture due to the presence of metastases. The T2 shortening due to SPIO accumulation was pronounced in normal nodes, allowing for significant increases in positive predictive values and accuracy of diagnosis of node metastases 3 (Fig. 2).…”
Section: Lymph Node Imagingmentioning
confidence: 99%
“…116 When used as a contrast agent in living subjects, adverse events from USPIO (dextran-coated SPIO) were noted as not serious, mild in severity, and short in duration. 3 The most common reactions were headache, back pain, vasodilatation, and hives. Magnetite biocompatibility has already been proven.…”
Section: Biocompatibilitymentioning
confidence: 99%
“…Also the introduction of lymph node specific contrast agents like ultrasmall particles iron oxide on magnetic resonance imaging (MRI) provides differentiation between benign and malignant lymph nodes in the head and neck and results are improving [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative analysis was performed 6 months after the completion of the SI measurement study and the criteria reported by previous studies for a diagnosis for USPIO-enhanced MRI was used: a lymph node with an area of high SI on T2-or T2*-weighted images after USPIO administration was considered malignant, and a node with a fatty hilum, a complete signal void, and speckles of granularity without a definite focus of high SI on T2-or T2*-weighted images after USPIO administration was considered nonmalignant (4,5), and a node with a central low SI on T2*-weighted MR imaging after USPIO administration was considered nonmalignant (6). The results of quantitative analysis for the 1.5 T and 3.0 T scanners were assigned to the two investigators.…”
Section: Qualitative Analysis For the Differentiation Of Benign And Mmentioning
confidence: 99%
“…Even though this technique is still not approved by regulatory agencies in North America and Europe, several studies have demonstrated enhanced sensitivity and specificity for malignant lymph node evaluation after the administration of ferumoxtran-10 (Combidex; AMAG Pharmaceuticals, Lexington, MA), a USPIO agent, for pelvic, breast, head and neck, and chest malignancies (4)(5)(6)(7). Diagnostic guidelines for the interpretation of USPIO-enhanced MRI have been reported and the results for the evaluation of malignant lymph nodes with sensitivities and specificities of 79%-91%, and 77%-98%, respectively, have been reported.…”
mentioning
confidence: 99%